2015
DOI: 10.1007/s11676-015-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Clonal variations in nutritional components of Pinus koreansis seeds collected from seed orchards in Northeastern China

Abstract: From four Korean pine (Pinus koraiensis) orchards, 60 clones were selected and analyzed for the fatty acid and amino acid components of the seeds to reveal the variations and correlations of the seed characteristics among the clonal source orchards and clones. The nutritional components of the seeds of the P. koraiensis trees exhibited rich genetic variation; the variation coefficient of the fatty acids was 2.24-66.83 %, while the variation coefficient of the amino acids was 14.70-38.88 %. Relatively high gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Especially, Korean pine nuts are the product of an edible woody oil tree species with oil content as high as 56.76%. The nutritional components of the seeds of the P. koraiensis trees exhibited rich variation; the variation coefficient of the fatty acids was 2.24%-66.83% [39]. Our research obtained 41,476 unigenes and 25,824 annotation information unigenes by assembly.…”
Section: Resultsmentioning
confidence: 83%
“…Especially, Korean pine nuts are the product of an edible woody oil tree species with oil content as high as 56.76%. The nutritional components of the seeds of the P. koraiensis trees exhibited rich variation; the variation coefficient of the fatty acids was 2.24%-66.83% [39]. Our research obtained 41,476 unigenes and 25,824 annotation information unigenes by assembly.…”
Section: Resultsmentioning
confidence: 83%
“…The results of Zhang et al. (2016) on Korean pine ( Pinus koreansis ) showed that oleic acid (C18:1) and linoleic acid (C18:2) were the most abundant fatty acids. Archontoulis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the oleic acid (C18:1) and linoleic acid (C18:2) account for the highest proportion agreed with previous reports . The results of Zhang et al (2016) on Korean pine (Pinus koreansis) showed that oleic acid (C18:1) and linoleic acid (C18:2) were the most abundant fatty acids. Archontoulis et al (2010) also found that the contents of oleic acid and linoleic acid accounted for 81.91% of the total fatty acids contents in the cardoon (Cynara cardunculus L.).…”
Section: Oil Content and Fatty Acid Analysismentioning
confidence: 99%
“…It is widely appreciated for its use in internal and external construction, particularly due to the high quality of its wood [3]. The nuts of this species are also used for a variety of nutritional products and therapeutics [4]. Because of its various economic benefits, along with its increasingly recognized environmental roles in CO 2 sequestration, water regulation and soil protection for plantations on slopes [5], the Korean pine has been extensively recommended for afforestation and reforestation projects [6].…”
Section: Introductionmentioning
confidence: 99%
“…were selected based only on their growth traits or wood properties to meet the demand for timber over the past several years [11]. However, with the official decree in 2016 against the cutting of natural forests, more attention has been paid to seeds and cones of P. koraiensis [4,12]. Considering only the seed yield, China is reported to have generated more than $250 million USD annually from pine nuts [13].…”
Section: Introductionmentioning
confidence: 99%